Balik Nama Sertipikat Hak Milik Atas Tanah Berdasarkan Akta Lelang Eksekusi Hak Tanggungan di Kota Pariaman - Heriyus, Anisa Noverina; Warman, Kurnia; Andora, Hengky (Universitas Ekasakti, 2023)
The mortgage execution auction occurs if the debtor defaults, the first mortgage holder has the right to sell the mortgage object on his own authority through a public auction and collect the settlement of his receivables from the proceeds of the sale. In this case the creditor is always the party that directly does have a legal relationship with the debtor through the agreement that they have entered into, of course they are ready with all the attitudes of the debtor, but what about the auction winner, in this case the auction winner is just an individual/legal entity legally and legally carry out sales and purchases in a manner determined and carried out based on law, the auction winner, who in this case becomes the buyer of the collateral object through auction, even gets a lawsuit from the debtor or other parties because he is dissatisfied and has his rights those who are harmed by the creditor's decision to carry out the auction. Of course, this needs to be reviewed again so that the auction winners do not become an outlet for any party's dissatisfaction with the auction of collateral items given to the creditor bank. This study aims to determine the execution of mortgage execution auctions, the process of transferring title certificates of property rights based on auctions, as well as legal protection guarantees for auction winners, the protection referred to here is legal protection that guarantees the auction winner's rights to the object won. From the results of this study it is known that the form of legal protection obtained by the auction winner is a court decision which says that the auction is legal and strengthens the rights of the auction winner over the object of the auction he won. Meanwhile, if the auction is canceled by the court due to law, in this case the legal protection that the winner of the auction gets is that he can demand payment of money for the auction object that has been deposited with the auction official, and can demand costs incurred if he has already registered the auction object.